2017
DOI: 10.1021/acscentsci.6b00371
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology-Driven Therapeutic Interventions in Wound Healing: Potential Uses and Applications

Abstract: The chronic nature and associated complications of nonhealing wounds have led to the emergence of nanotechnology-based therapies that aim at facilitating the healing process and ultimately repairing the injured tissue. A number of engineered nanotechnologies have been proposed demonstrating unique properties and multiple functions that address specific problems associated with wound repair mechanisms. In this outlook, we highlight the most recently developed nanotechnology-based therapeutic agents and assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
289
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 422 publications
(292 citation statements)
references
References 135 publications
(274 reference statements)
0
289
0
3
Order By: Relevance
“…In a recent study by Malone et al, at least 78 % of chronic wounds were found to contain biofilm . Managing the bacterial load in wounds is an important factor to facilitate tissue repair …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent study by Malone et al, at least 78 % of chronic wounds were found to contain biofilm . Managing the bacterial load in wounds is an important factor to facilitate tissue repair …”
Section: Introductionmentioning
confidence: 99%
“…There are a number of wound dressings that are available as primary or secondary therapies for both acute and chronic wounds. Besides their role in providing a moist environment for optimal wound healing, they are able to absorb excess wound fluid, assist in autolytic wound debridement, provide a barrier to wound pathogens, and reduce the bacterial load …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro studies have shown that primary cells isolated from chronic wounds maintain tissue characteristics and show altered proliferative and migratory capacity accompanied with an inability to respond to wound‐healing stimuli such as growth factors and cytokines . While the actions of multiple cell types are tightly regulated by growth factors, cytokines and signalling molecules during the acute wound‐healing process, this regulation, and interplay between different signalling factors, is dysregulated in chronic wounds . Furthermore, chronic wounds exhibit high levels of metalloproteinases (MMP) and a perturbed ratio between MMP and tissue inhibitors of metalloproteinases (TIMPs), which contribute to a hostile wound environment, lack of growth factor and cytokine signalling and subsequently delayed healing (Table ) .…”
Section: What Did We Learn So Far From Studies Utilizing Human Woundmentioning
confidence: 99%